THE NORTHERN CASPIAN ON CHINA’S GEOPOLITICAL AGENDA - BABAYAN, David (CENTRAL ASIA AND THE CAUCASUS, 2012)
Everyone knows that in addition to its keen interest in the Southern and Northern Caucasus, the People’s Republic of China (PRC) is also active in Central Asia, another area of its geopolitical interests. Much has and is being written about this, but for some reason no one has examined China’s presence in the Northern Caspian (I have in mind the Atyrau Region of Kazakhstan, the relations with which are part and parcel of China’s Central Asian policy, and the Astrakhan Region and Kalmykia of Russia).Here I will dwell on Chinese strategy in the two latter regions of the Russian Federation, that is, in the Russian part of the Northern Caspian. As a sort of corridor or link between Central Asia and the Caucasus with a multitude of ties between them and this part of Russia, the region is of immense geopolitical importance for Beijing.Indeed, the Northern Caspian offers a lot of opportunities for China, ranging from the economy to the humanitarian and religious spheres; its strategic location is very important for China’s security. This means that this region is one of the components of China’s Central Asian and Caucasian geopolitics.